The organization of intrinsic brain activity differs between genders: A resting‐state fMRI study in a large cohort of young healthy subjects. Issue 6 (22nd February 2012) - Filippi, Massimo; Valsasina, Paola; Misci, Paolo; Falini, Andrea; Comi, Giancarlo; Rocca, Maria A.
Abstract Objectives: To investigate, using resting state (RS) functional MRI (fMRI), gender‐related differences of functional connectivity (FC) and functional network connectivity (FNC) of the human brain. Experimental design: One‐hundred and four young healthy subjects (48/56 men/women), aged between 20 and 29 years, underwent a 10‐min RS fMRI acquisition. Independent component analysis (ICA) and statistical parametric mapping were used to assess gender‐related differences in RSNs, with and without correction for regional gray matter (GM) volume. The relationships among all RSNs was also assessed using a FNC method. Principal observations: For all networks, significant between‐group differences of RS activity were found. Between‐group comparisons of RSNs changed when adjusting for GM volume, as follows: (1) there was only marginal effect on the analysis of sensory (i.e., sensorimotor, visual, and auditory) networks; and (2) there was a significantly increased difference when cognitive networks (apart from one related to attention) were considered. Compared with women, men experienced increased FC in parietal and occipital regions in most RSNs, whereas women experienced a higher RS FC in frontal and temporal regions, and in the cerebellum. When compared to women, increased FNC was found in men between several cognitive and sensory networks, whereas women showed an increased FNC only between attention and right working‐memory networks. Conclusions: The organization of intrinsic FC and FNC differ between genders. The detected differences could contribute to the understanding of the known between‐gender variation in task‐related recruitments, and the patterns of abnormalities detected in neurologic and psychiatric diseases with a gender prevalence. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.